Hubungan Literasi Numerasi dengan Kemampuan Berpikir Kritis Siswa Madrasah Ibtidaiyah di Sidoarjo Jawa Timur - Dewi Yulia Putri S.; Hanik Yuni Alfiyah (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims (1) to find out how numeracy literacy of Madrasah Ibtidaiyah students in Sidoarjo, East Java, (2) to find out how critical thinking skills of Madrasah Ibtidaiyah students in Sidoarjo, East Java, (3) to find out whether there is a relationship between literacy and critical thinking skills of Madrasah Ibtidaiyah students in Sidoarjo, East Java. This research is a correlation research with a quantitative approach with types of Product moment correlation research. The research was conducted in MI Roudlotul Islamiyah Wonoayu sub-district and MI TANADA Waru sub-district. Researchers took 18% of the population i.e. 131 students out of 729 students. The results of the research that have been conducted are known that the correlation efficiency between numeracy literacy (X) and critical thinking skills (Y) is 0.5391 which shows a moderate level of correlation. The correlation efficiency is positive which means there is a positive relationship. The correlation that occurs is significant because the calculated value is greater than ttable, which is 0.14430.1716. Therefore, the null hypothesis that states there is no relationship between numeracy literacy and the critical thinking ability of Madrasah Ibtidaiyah students in Sidoarjo, East Java is